Internalisasi Nilai-Nilai Tri Satya dan Dasa Darma pada Mata Pelajaran Pendidikan Agama Islam (PAI) di Sekolah Dasar Negeri 1 Kutowinangun - Anang Makrup; Faisal Faisal; Devi Yaniar Wi Hargina (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
The research objectives are : Khowing the Internalize of the values of Tri Satya and Dasa Darma in state elementary school (SD N) 1 Kutowinangun. (2) Knowing the syinergistic relationship between the values of Tri Satya and Dasa darma in state elementary school (SD N) 1 Kutowinangun.The research method used is qualitative research methods. Data analysis techniques used are observation, interviews, and document. Data analysis techniques used are data reduction, data presention, data verification and conclusions.Based on the research, it can be concluded as follows : The values of Tri Satya and Dasa Darma in Islamic Religious Education subjects include growing a sense of love for Allah SWT., helping behavior, loving nature, respecting elders, loving the homeland, being obedient to teachers, diligent in going to school, frugal, disciplined character and well-behaved. The synergy of the values of Tri Satya and Dasa Darma in Islamic Religious Education subjects can be seen from activities such as opening and closing ceremonies, delivering theory, big games, love of nature activities and Scouting Skill activities.